Why labour market performance differed across countries: the impact of institutions and labour market policy - Österreichisches Institut für Wirtschaftsforschung, Vienna; Aiginger, Karl; Horvath, Gerard Thomas; Mahringer, Helmut (Vienna, 2011)
"This paper investigates the performance of labour markets during the recent crisis. While the crisis had started rather simultaneously across regions and countries, the length and deepness finally proved very heterogeneous. Some countries still have not rebounded, in others inflationary pressure has become a severe problem after output had surpassed pre-crisis level by far. The same holds for labour markets: In some countries employment is now above its pre-crisis peak and unemployment stable or falling, in others the unemployment rate is persistently near or above 10 percent. This paper investigates to which extent labour market performance during the crisis depended on 1. macroeconomic conditions prevailing at the start of the crisis, 2. structural characteristics of the economies, and 3. labour market institutions and policy. Labour Market Performance is analysed against these determinants alone and relative to output performance. Specific emphasis is given to cases in which cross country differentials in labour market performance do not go in parallel to output performance. The growth performance in the USA was better than average, the labour market was deeply affected and has still not rebounded. On the other side Germany experienced a steeper output loss, but had a better labour market performance. Output performance as well as labour market performance is measured by a composite indicator summarising several output and labour indicators. It was derived by Principal Component analyses."